EFEKTIFITAS PELATIHAN PEER EDUCATOR TERHADAP PENINGKATAN PENGETAHUAN, KETERAMPILAN DAN PERUBAHAN SKOR BODY IMAGE REMAJA PUTRI SMAN 4 PURWOKERTO - Rima Sumayyah Ahmad; Erna Kusuma Wati (Jurnal Gizi dan Pangan Soedirman, 2018)
Body image is one of the causes of eating behavior deviates in addition to genetic factors and low self confidence. Knowing the effectiveness of peer educators training in improving the knowledge, skills and scores of body image of young women in SMAN 4 Purwokerto. This study used a quasi-experimental design with one group pretest posttest. The study was conducted in SMA Negeri 4 Purwokerto. Samples were 39 young women and were aken by purposive sampling. The results of statistical tests using the Wilcoxon test was obtained grades A Sym. Sig. (2-tailed) = 0.000 (<0.05) in all study variables means statistically there are differences in knowledge of body image, peer educator knowledge, body image score and skills of young women SMAN 4 Purwokerto significant before and after training. Peer educators training is effective in improving knowledge, skills and scores of body image of young women in SMAN 4 Purwokerto